Problemy rozwoju gospodarczego Ziem Odzyskanych w pierwszym powojennym dziesięcioleciu (1945-1955) = Problems of economic development in the Regained Territories during the first ten years after the war (1945-1955) - Skobelski, Robert (1968- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Economic development of the Regained Territories in the first ten years after the war proceeded under very complex political and social conditions. The damage and devastation of those areas as well as the migration of people hindered enormously the incorporation of these lands into the Polish economic organism. The situation was additionally complicated by the post-war chaos and limited possibilities of the state, which at the time did not possess adequate financial and material sources that could be allocated for rebuilding.
Keywords: Ziemie Odzyskane; rozwój gospodarczy; Plan 3-letni; Plan 6-letni; historia; po 1944 r.